2020
DOI: 10.1177/0013124520928610
|View full text |Cite
|
Sign up to set email alerts
|

They’re Moving in Spaces They’re Not Used to: Examining the Racialized Experiences of African American Students in a High School STEAM Academy

Abstract: In this study, we explored how an urban high school with a STEAM (Science, Technology, Arts, and Mathematics) theme approached racialized student experiences as learning opportunities. We were interested in documenting curricular and pedagogical practices, and the mission of the STEAM Academy, which was aimed at exposing African American/Black students to possibilities beyond the school including university settings and workplace environments (through job shadowing and internships). Based on the perspectives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…These imbalances result in a double mismatch for Black boys. Equally poignant, when we consider who is thriving in schools, it is White girls—a double congruence that supports the increasing volume of work on diversifying the education profession because representation and racial matching matter (Fletcher, 2014; Fletcher & Hernandez‐Gantes, 2021). Minoritized students achieve at higher levels when they have educators who look like them (Fletcher & Moore, 2021; Fletcher & Tan, 2021), who share their culture (Easton‐Brooks, 2019; Erickson, 2004; Hines, Fletcher, et al., 2022), and who hold high expectations of them (Ford, 2011).…”
Section: Educator Discretion: the Effects Of Deficit Thinkingmentioning
confidence: 99%
“…These imbalances result in a double mismatch for Black boys. Equally poignant, when we consider who is thriving in schools, it is White girls—a double congruence that supports the increasing volume of work on diversifying the education profession because representation and racial matching matter (Fletcher, 2014; Fletcher & Hernandez‐Gantes, 2021). Minoritized students achieve at higher levels when they have educators who look like them (Fletcher & Moore, 2021; Fletcher & Tan, 2021), who share their culture (Easton‐Brooks, 2019; Erickson, 2004; Hines, Fletcher, et al., 2022), and who hold high expectations of them (Ford, 2011).…”
Section: Educator Discretion: the Effects Of Deficit Thinkingmentioning
confidence: 99%
“…Nevertheless, Fletcher and Hernandez‐Gantes (2021) examined how an urban high school with a STEAM (Science, Technology, Arts, and Mathematics) theme approached racialized student experiences as learning opportunities. The researchers were interested in documenting curricular and pedagogical practices, and the mission of the STEAM Academy, which was aimed at exposing Black students to possibilities beyond the school including university settings and workplace environments (through job shadowing and internships).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Shure et al (2019) explored the relationship between school counselor recommendations and student cultural behavioral styles and found that school counselor bias and low expectations of students of color (African American) contributed to educational disproportionality. Similarly, Fletcher and Hernandez-Gantes (2021) pointed to teachers' cultural incompetency which sometimes hinders students of color's academic growth. For example, Fletcher et al found that when teachers and administrators developed more racially focused pedagogy; that is, they took a social justice approach to education, African American students in STEAM programs (Science, Technology, Arts, and Mathematics) were more successful.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) explored the relationship between school counselor recommendations and student cultural behavioral styles and found that school counselor bias and low expectations of students of color (African American) contributed to educational disproportionality. Similarly, Fletcher and Hernandez‐Gantes (2021) pointed to teachers’ cultural incompetency which sometimes hinders students of color's academic growth. For example, Fletcher et al.…”
Section: Introductionmentioning
confidence: 99%